THE INFLUENCE OF GROUP COUNSELING SERVICES ON THE SELF-MANAGEMENT OF CLASS X STUDENTS AT SINAR HUSNI MEDAN HELVETIA PRIVATE HIGH SCHOOL - Nurul Annisa (BRIGHT VISION Journal of Language and Education, 2024)
This research aims to determine: the effect of group counseling services on the self-management of class X students at Sinar Husni Medan Helvetia Private High School. This type of research is quantitative quasi-experiment (quasi-experiment) with pre-test and post-test one group design. The subjects of this research were 84 class X students at Sinar Husni High School Medan Helvetia. The sampling technique used purposive sampling. This research data was taken using a student self-management questionnaire with 25 valid and reliable question items, then the data was analyzed using the SPSS test. Pre-test data on self-management obtained an average score of 78.24. Meanwhile, post test data on self-management obtained an average score of 84.04. This means that the average score of students after receiving group counseling services is higher than before receiving group counseling services in self-management. From data analysis, it is obtained that Fcount = 51.123 with a = 0.05 and Ftable = 3.95. From these data it can be seen that Fcount > Ftable where 51.123 > 3.95. This means that the hypothesis is accepted. Group counseling services contributed 38.4% to improving self-management for class X students at Sinar Husni High School Medan Helvetia. This shows that there is an influence of providing group guidance services to overcome the self-management of class X students at Sinar Husni High School Medan Helvetia or the hypothesis can be accepted.